Answer:
f(g(-1)) = -6
Explanation:
* Lets explain how to solve the problem
- The problem is about the composite function
- A composite function is a function that depends on another function.
- A composite function is created when one function is substituted into
another function.
- Ex: f(g(x)) is the composite function that is formed when g(x) is
substituted for x in f(x)
* lets solve the problem
∵ f(x) = x - 7
∵ g(x) = x²
- We want to find f(g(-1))
* At first lets find g(-1) by substitute x in the function g(x) by -1
∵ g(x) = x²
∵ x = -1
∴ g(-1) = (-1)² = 1
* Now we want to find f(g(-1)), then we will substitute x in f(x) by
the value of g(-1)
∵ g(-1) = 1
∵ f(x) = x - 7
∴ f(g(-1)) = f(1)
∵ f(1) = 1 - 7 = -6
∴ f(g(-1)) = -6